Allergic to Pool Water - Harma Stenveld (Elsevier, 2012)
To identify the allergy problem of a 36-year old swimming instructor, who experiences heavy itching and rashes whenever she comes in contact with pool water. Patch tests were performed with European standard series and materials from the work floor. A positive patch test to aluminum chloride and flocculant was observed. Occupational dermatitis is, based on a contact allergy to aluminum chloride in the flocculant.